Neuromuscolar taping in multiple sclerosis. A pilot study - Costantino, C.; Licari, O.; Granella, et al., F. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim of the work: Neuromuscular Taping (NT) is a relatively new device that induces micro-movements by stimulating receptors in the skin. The aim of this study was to analyze the effect of the application of Neuromuscular Taping (NT) on motor performance and quality of life in a cohort of multiple sclerosis (MS) patients. Methods: Twenty MS patients with Expanded Disability Status Scale ≤ 4 (EDSS); clinically stable disease; absence of relapses during the last 3 months; absence of rehabilitation treatment or symptomatic drugs acting on muscular tone or fatigue for at least 2 months; a stable disease modifying treatment for at least 3 months; were treated with the application of NT. It was applied four times at 4-day intervals on the weakest side of the hamstrings muscles. The treatment efficacy on motor performance was evaluated by the six minute walking test (6MWT), measured at the beginning of treatment (T0), at the end of NT application (T1), and three weeks after the last treatment application (T2). Moreover, Short Form 36 health survey (SF-36) was administered to evaluate the quality of life. Results: The mean distance covered during the 6MWT improved significantly between T0 and the successive T1 and T2 measurements, passing from 342.6±148.9 mt at T0 to 395.8±146.0 mt at T2 (p=0.03). The SF-36 showed a statistically significant improvement in most items. Conclusions: The application of NT was able to improve significantly the motor performance and the quality of life in our small case series of MS patients.